Influence of the Shaping Process on the Tensile Properties of Steel Reinforcement Bars Carbon Steel Grades BJTP24 and BJTS40 - Handika, Nuraziz; Idhar, Ridha Amalia; Sjah, Jessica; Arijoeni, Essy; Tjahjono, Elly (UI Scholars Hub, 2020)
According to the current applicable national standard in Indonesia, i.e. SNI 07 2529 1991, in addition to the limitation on the loading rate, the steel bar must be reduced, formed, or lathed, as part of the shaping process of samples. This study determined and compared the effect of the shaping process on the yield strength, ultimate strength, and percent elongation by conducting tensile tests of steel bar grade BJTS40, i.e. deformed bar type of steel, and grade BJTP24, i.e., plain bar type of steel. Three diameters of the deformed bar (BJTS40) and one diameter of the plain bar (BJTP24) were used. Samples of the bars were taken randomly from a local distributor in the Greater Jakarta area. Each 1 m of the bar is divided into two, i.e. one end being the non-shaped sample and the other end being the shaped sample. Tensile tests of these two sides were conducted. This study determined that the shaping process influences the results of the tensile test, particularly the variation of percent elongation. Moreover, the effects of the shaping process can be inferred from the high coefficients of variation of yield strength (4.33%) and ultimate strength (2.40%) of the shaped sample. The results of this study, which elucidate the effects of the shaping process on tensile tests, can be used as an information resource in engineering practice.